Identification of the CFTR c.1666A>G Mutation in Hereditary Inclusion Body Myopathy Using Next-Generation Sequencing Analysis - Lu, Yan; Da, Yu-Wei; Zhang, Yong-Biao; Li, Xin-Gang; Wang, Min; Di, Li; Pang, Mi; Lei, Lin (Frontiers in Neuroscience, 2018)
Hereditary inclusion body myopathy (HIBM) is an ultra-rare severely disabling autosomal recessive adult onset muscle disease which affects roughly one to three individuals per million worldwide. Our previous study reported a new subtype of HIBM linked to the susceptibility locus at 7q22.1-31.1. The present study is aimed to identify the candidate gene responsible for the phenotype in HIBM pedigree. After multipoint linkage analysis, we performed targeted capture sequencing on 16 members and whole-exome sequencing (WES) on 5 members. Bioinformatics filtering was performed to prioritize the candidate pathogenic gene variants, which were further genotyped by Sanger sequencing. The results of multipoint linkage analysis again showed that the highest peak of LOD score (4.70) was on chromosome 7q22.1–31.1. We identified 2 and 22 candidates using targeted capture sequencing and WES,, in which only the CFTRc.1666A>G mutation was well cosegregated with the HIBM phenotype. We did not detect mRNA expression differences in CFTR in skeletal muscle of the affected proband using transcriptome analysis. . We have no way to collect other pedigree of this new subtype of HIBM. So the mutation was detected in three patients with duchenne muscular dystrophyn (DMD) and five patients with limb-girdle muscular dystrophy (LGMD), we suggested that the CFTRc.1666A>G may be a marker which has strong linkage disequilibrium with the really causative gene in the HIBM family.